Reconnecting body and soul: the nexus of spirituality, compassion and empathy in medical education - Philip A Pizzo (Academic Medicine, 2026)
Abstract Spirituality, faith or religion are important to the majority of Americans. Although spirituality and religion are determinants of health and disease outcome, they are not prominently or consistently included in medical education. Students are receptive to learning about spirituality, and most physicians acknowledge its importance, but few discuss it with their patients. Courses or programs that include spirituality and its assessment as a medical competency have been attempted but not sustained, and most students and trainees do not feel adequately educated about spirituality. As a physician-scientist, educator and academic leader who believed he was attentive to the biopsychosocial model of care, exploring and responding to the spiritual or religious beliefs of patients was not prominent in my education or the care I provided. This changed when I trained as a chaplain after many decades in medicine, and recognized how important spiritualty was to the patients I visited. To better understand this I explored what might be done to remedy this gap in medical education and in the care of the whole patient, body and soul. In this Commentary I offer some recommendations. that include the importance of partnerships in education and care between physicians and chaplains as a way of providing students with tools to improve their awareness of the importance of spirituality in the patients they are caring for, as well as to improve their skills in empathy and compassion. Such collaborations can also teach students ways of being present and listening to their patient’s fears and concerns about the impact of their disease. In addition, such partnerships can also help medical students reflect on their personal reaction to the illnesses of those they serve. Seeking ways to improve the connection of body and soul though the nexus of spiritualty, compassion and empathy, facilitates patient-centered care over disease-centered care, and thus care of the whole patient.